In situ study of spray deposited titania photoanodes for scalable fabrication of solid-state dye-sensitized solar cells. (October 2017) - Song, Lin; Wang, Weijia; Körstgens, Volker; Moseguí González, Daniel; Löhrer, Franziska C.; Schaffer, Christoph J.; Schlipf, Johannes; Peters, Kristina; Bein, Thomas; Fattakhova-Rohlfing, Dina; Roth, Stephan V.; Müller-Buschbaum, Peter
Abstract: Spray coating, a cost-effective and scalable technique, has been employed for fabricating titania films for solid-state dye-sensitized solar cells (ssDSSCs). The spray deposition of films is inherently based on kinetic processes with great complexity, which poses great challenges in its understanding. In the present work, the kinetics of the structure evolution of deposited films are investigated by in situ grazing-incidence small-angle x-ray scattering during spray deposition. The spray-solution is prepared via a polystyrene-block-polyethylene oxide (PS-b-PEO) template assisted sol-gel synthesis. It is turned into nanostructured titania/PS-b-PEO composite films via spray deposition. The information about nanostructure length scales of the composite film is obtained in real-time and in situ, revealing the morphological evolution during the spray deposition. The resulting mesoporous titania films serve as photoanodes of ssDSSCs, which couple with the solution-cast hole transport layer to form the active layers. The well working ssDSSCs demonstrate the successful use of spray deposition as a large-scale manufacturing process for photoanodes. Graphical abstract: The complex spray kinetics are monitored by the morphological evolution of titania/PS-b-PEO composite films with real-time and in situ grazing incidence small-angle x-ray scattering during spray deposition. The active layer of solid-state dye-sensitized solar cells is produced based on spray coating and solution casting, giving a bright application prospect for upscale towards industrial processes. Highlights: Structure evolution of titania/PS-b-PEO composite films is studied by in situ grazing-incidence small-angle x-ray scattering during spray deposition. Surface and inner film morphologies of the deposited films are compared before and after high-temperature calcination. Titania films serve as photoanodes for solid-state dye-sensitized solar cells fabricated via large-scale manufacturing processes.